Ausgrabungen in der Kleinsiedlung Babunjë bei Apollonia (Albanien).: Bericht zu den Kampagnen 2018–2019 - Fiedler, Manuel; Lahi, Bashkim; Shehi, Eduard; Pánczél, Szilamér-Péter; Velo, Klodian; Döhner, Gregor (Römische Mitteilungen, 2021)
Field research at Babunjë, a small fortified settlement of ca. 5 ha lying between the Corinthian-Corcyraian colonies of Apollonia and Epidamnos, seeks to achieve a better understanding of the colonial settlement structure at the eastern coast of the southern Adriatic (and further south along the Ionian Sea). Babunjë was founded at the end of the 6th century BC and was abandoned in the last decades of the 4th century BC. The site had a fortification with a ‚bastion‘ or unusual large tower which was built some decades after Babunjë’s foundation. A planned urban layout shows long, narrow insulae with single rows of house-plots. A two-roomed house was excavated completely. Small settlements like Babunjë were, after the large colonies, most probably an important part of the colonial settlement structure on this coast.